Improved electrochemical properties and kinetics of an LiMn2O4-based cathode co-modified via Cu doping with truncated octahedron morphology. (12th June 2020) - Wang, Shimin; Liu, Honglei; Xiang, Mingwu; Guo, Junming; Bai, Wei; Bai, Hongli; Liu, Xiaofang; Su, Changwei
Abstract : Spinel LiMn2 O4 has been widely investigated as a cathode material for lithium-ion batteries, but it suffers from a limited cycle life due to the dissolution of Mn and structural distortion. Abstract : Spinel LiMn2 O4 has been widely investigated as a cathode material for lithium-ion batteries, but it suffers from a limited cycle life due to the dissolution of Mn and structural distortion. Herein, a facile solution combustion approach was used to prepare a spinel LiCu0.05 Mn1.95 O4 cathode material with truncated octahedron morphology. This unique octahedral structure endowed LiCu0.05 Mn1.95 O4 with a small portion of orientated 110 and 100 surfaces aligned to the favorable diffusion channels of Li ions, resulting in enhanced kinetics. Moreover, Cu-doping increased the average oxidation state of manganese, which effectively restrained the Jahn–Teller distortion. Consequently, the obtained sample showed improved electrochemical cyclability and structural stability. The initial discharge capacities of 110.2 and 90.2 mA h g −1 were delivered at 1C and 10C, with the corresponding capacity retentions of 66.1% and 81.5% after 1000 cycles, respectively. Additionally, enhanced high-temperature electrochemical properties were achieved at 1C and 55 °C after 500 cycles. These excellent electrochemical performances are also ascribed to the low activation energy (22.57 kJ mol −1 ) and a relatively high Li + diffusion coefficient (1.84 × 10 −15 cm 2 s −1 ).